Enhancing Arabic Proficiency through Structured Language Planning and Curriculum Integration/ Ta'ziz al-Kafa'ah al-Lughawiyyah al-'Arabiyyah min Khilal al-Takhtit al-Lughawi al-Munazzam wa Takamul al-Manahij al-Dirasiyyah - Wardhana, Delly; Bahruddin, Uril; Imaduddin, M Firdaus; Gareeb Allah Babiker Mustafa Babiker (Universitas Islam Negeri Raden Intan Lampung, 2025)
The lack of well structured Arabic language planning in several Islamic educational institutions has led to fragmented learning and minimal real-world application of the language. This study had the urgency to explore the deeper causes of this issue and analyze how intentional language policy which is thoughtfully implemented can improve learners’ Arabic proficiency, connect language use to Islamic studies, and build a more immersive educational environment. This qualitative study critically analyzed the mid-level Arabic language planning policy at the Imam Shafi'i Islamic Boarding School in Lampung. Using a qualitative case study design, the data were collected through classroom observations, semi-structured interviews with administrators, eight teachers, and twenty students, as well as curriculum and institutional document analysis. The findings revealed three core aspects of language planning at the islamic institution: (1) a strong emphasis on achieving proficiency in both spoken and written Arabic; (2) the integration of Arabic language materials with Islamic studies through a thoughtfully selected curriculum; and (3) the development of an Arabic-speaking environment. This study offered practical insights into how structured Arabic language planning can improve student proficiency in Islamic boarding schools. By examining the case of Imam Shafi'i Islamic Boarding School, it showed how integrating Arabic instruction with Islamic studies and building an immersive language environment can lead to more effective learning. The findings provided a model that other Islamic institutions can adapt to develop clearer language goals, strengthen teaching strategies, and create supportive environments for Arabic learning.